Komunikasi Politik Lewat Kartun: Sindiran, Kritik, Dukungan, & Perlawanan - HADI OKI CAHYADI (Politeia: Jurnal Ilmu Politik, 2010)
This study description about relation between cartoon and politics in general, and description they dependability relationship in political history in Indonesia. In fact, cartoon, become indi-visible part from event and phenomenon political. Cartoon have symbolic meaning that show existence of suggestion, criticism, support and resistance to political object like executive, leg-islative, political party, and society. In consequence, its not wrong if told that cartoon existence in a country becomes indicator to see weather seriously a country do democracy or not. Car-toon is way to submit political message indirectly, although its comments not always will be im-pressing positive. But, this assessment is relative because cartoon can used as the government propaganda. Cartoon history in Indonesia indicates that at a period of government Soeharto cartoon publication gets tight monitoring. At a period of government Soekarno, it’s becomes political propaganda tool, both domestic and international relation. So, besides as the work of art and political art, in politics, cartoon is very strategic communication means.Keywords: Cartoon, Political communications, Political art.